2007
DOI: 10.1158/1078-0432.ccr-06-2363
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3+ Regulatory T Cells Affect the Development and Progression of Hepatocarcinogenesis

Abstract: Purpose: Tumor-infiltrating lymphocytes represent the host immune response to cancer. CD4+ CD25 + FOXP3 + regulatory T cells (Tregs) suppress the immune reaction. The aim of the present study was to investigate the clinicopathologic significance and roles of Tregs and CD8 + Tcells during hepatocarcinogenesis. Experimental Design: We examined the infiltration of FOXP3 + Tregs and CD8 + T cells in the tumor stroma and nontumorous liver parenchyma using 323 hepatic nodules including precursor lesions, early hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
285
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(315 citation statements)
references
References 41 publications
22
285
3
5
Order By: Relevance
“…Previous experimental study reported a similar finding (Kobayashi et al, 2007). Moreover, we also found the frequency of CD3-CD56+, CD3-CD57+ and CD3+CD8+ cells of the patients with the metastasis less than 12 months were lower than those without metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Previous experimental study reported a similar finding (Kobayashi et al, 2007). Moreover, we also found the frequency of CD3-CD56+, CD3-CD57+ and CD3+CD8+ cells of the patients with the metastasis less than 12 months were lower than those without metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the immunosuppression is produced. This suggests that high expression of Treg cells can promote the development of tumor, and affect the prognosis for patients (Woo et al, 2001;Gray et al, 2003;Kono et al, 2006;Hiraoka et al, 2006;Kobayashi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since the amount of FOXP3 + cells did not show association with any of the studied parameters: patient age or gender, tumor thickness, location, histological type, ulceration and, most importantly, the outcome of the disease, as mentioned above, FOXP3 + cell infiltration in the primary tumor does not seem to have a significant impact on the course of the disease in cutaneous melanoma. Previous studies aiming at the clinical relevance of tumor-infiltrating Tregs have given rise to contradictory results, showing correlation with poor outcome in some cancer types [5][6][7][8][9] but no association or even correlation with improved survival in others [10][11][12][13][14][15][16][17]21]. It could be suggested that each tumor type behaves differently in this context [4], depending perhaps on other players on the scene of antitumor immune reactions and their complex functional interrelationships with Tregs as well as with tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the prognostic role of tumor-infiltrating Tregs are inconclusive; while in some cancer types their increased level has been correlated with poor outcome, as in the case of ovarian, breast, pancreatic and hepatocellular carcinomas [5][6][7][8][9], in others including prostate and renal cancers no significant associations were found [10,11], and in the case of head and neck carcinomas, colorectal cancer, as well as in several lymphoma types a marked infiltration by Tregs showed correlation with improved survival [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%